EVALUASI DAN REDESIGN WEBSITE STARTUP AQIBERS MENGGUNAKAN SYSTEM USABILITY SCALE - Meilinda Sudjaja, dinda (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2024)
A user-friendly and effective website is a key element in digital startup success. This research aims to evaluate the usability of the Aqibers startup website using the System Usability Scale (SUS), a tool commonly used to measure user experience. The research methodology involves collecting data from respondents using the Aqibers website, then measuring it using SUS. The evaluation results show that there are several critical areas that require improvement to improve the overall user experience. Areas identified included complicated navigation, less intuitive interface design, and difficulty in finding relevant information. Based on the results of this evaluation, a website redesign was carried out with a focus on aspects that needed improvement, such as simplifying navigation, improving visual aesthetics, and increasing content accessibility. After the redesign, SUS measurements were carried out again to see the improvements achieved. The results showed a significant increase in usability scores, indicating that the changes made were successful in improving the user experience. This research concludes that implementing SUS-based evaluation and redesign can increase the level of website usability, which ultimately supports increasing startup performance in providing services to its users, as well as increasing user satisfaction and loyalty.